Qualitative Analysis of Phytochemical Compounds in Turmeric Powder as Functional Drink - Megananda, Rafaella Chandraseta; Primiani, Cicilia Novi; Anindhita, Mentari Nabila (Universitas Sultan Ageng Tirtayasa, 2024)
Jamu is an Indonesian culture still preserved by the community as an alternative treatment. One of the natural ingredients often used in herbal medicine is turmeric, which has various phytochemical compounds that benefit the body. This study examines the content of tannins, alkaloids, and saponins in traditional (conventional) instant powdered turmeric drinks and factory-made (commercial) instant sour turmeric powder drinks. Analysis of the phytochemical compounds in both samples was carried out qualitatively with various reagents used. Qualitative analysis was conducted based on changes in color or appearance in both instances. Based on the research conducted shows that, conventional and commercial turmeric powder is suspected of not containing tannin compounds but saponins and alkaloid compounds. The color analysis results show that traditional turmeric powder has darker color characteristics than commercial turmeric powder. It means that turmeric powder has phytochemical compounds, so it has the potential to be a functional drink that is beneficial to health.